2013
DOI: 10.1159/000356228
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental and Genetic Predictors of Suicide Attempt and Self-Mutilation

Abstract: Background and Aims: Literature findings mainly support the notion that suicide attempts (SA) and self-mutilating behavior (SMB) are distinct behaviors, although they may share common psychopathological features. In the present paper we aimed to identify behavioral phenotypes in patients with SA, SMB, or both (SAM) and to analyze the association with candidate genes. Methods: One hundred forty-two inpatients with a history of SA (n = 86), SMB (n = 22), and SAM (n = 39) were included in this study. Subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…First, several studies have targeted a polymorphism of the serotonin-transporter linked promoter region (5-HTTLPR). No significant main effects of the 5-HTTLPR on the occurrence of NSSI were found in a sample of male prisoners (Gorodetsky et al, 2016) or between groups of adults receiving inpatient care who reported a history of suicide attempts or NSSI (Dell'osso et al, 2013). Steiger et al (2011) failed to find a relationship between variants of the 5-HTTLPR and self-harming behavior, defined as NSSI and/or suicidal behavior, in independent samples of adult females with eating disorders.…”
Section: Genesmentioning
confidence: 90%
See 1 more Smart Citation
“…First, several studies have targeted a polymorphism of the serotonin-transporter linked promoter region (5-HTTLPR). No significant main effects of the 5-HTTLPR on the occurrence of NSSI were found in a sample of male prisoners (Gorodetsky et al, 2016) or between groups of adults receiving inpatient care who reported a history of suicide attempts or NSSI (Dell'osso et al, 2013). Steiger et al (2011) failed to find a relationship between variants of the 5-HTTLPR and self-harming behavior, defined as NSSI and/or suicidal behavior, in independent samples of adult females with eating disorders.…”
Section: Genesmentioning
confidence: 90%
“…However, in the same study, high-function variants of the monoamine oxidase A (MAOA) gene were associated with increased risk of self-harming behavior (Steiger et al, 2011). With regard to polymorphisms of the catechol-O-methyl transferase (COMT) gene, no significant differences were found between groups of adults receiving inpatient care who reported a history of suicide attempts or engagement in NSSI (Dell'osso et al, 2013). In contrast, Bernegger et al (2018) found a haplotype of COMT polymorphisms (consisting of rs737865, rs6269, and rs4633) was associated with NSSI among adults with affective disorders.…”
Section: Genesmentioning
confidence: 93%
“…High comorbidity has been observed between suicide attempts and self-mutilation (Dulit et al , 1994, Klonsky et al , 2013, Nelson & Grunebaum, 1971, Nock et al , 2006). Persistent self-mutilation may predict repeated suicide attempts (Dell'osso et al , 2013, Klonsky et al , 2013). …”
Section: Introductionmentioning
confidence: 99%